Analysis of Changes in the Learning System of MTS YPI Al-Hidayah Lubuk Pakam Students Due to the Covid-19 Pandemic - Sophia Rahmadhani; Nuri Aslami (Journal of Indonesian Management, 2022)
Learning is very meaningful because through learning can be obtained the base of quality people's energy. Learning is also a very meaningful way to develop positive character for people, through good learning will produce smart people with good learning and good actions. However, several countries are currently being hit by an outbreak of the corona virus that causes COVID19, and one of the countries that has been affected by the virus is Indonesia. The impact of the corona virus outbreak on learning is the conversion of the upgrading system to an online system. The purpose of this research is to analyze the change in the upgrading system of MTS YPI AL HIDAYAH students in Lubuk Pakam. This research uses an online questionnaire procedure. In this research, 50 students participated. This survey shares facts about the advantages and disadvantages of the online upgrading system felt by students and teachers at MTS YPI Al-Hidayah Lubuk Pakam. From 50 respondents, 35 students or 75 percent of students feel that they do not master that 15 students or 25 percent create better descriptions by practicing online. Students feel unsafe to practice in because they cannot ask the teacher directly like in class. They can actually ask questions online, but they can't master the teacher's explanation because they don't have to be in direct contact. For the results of the questionnaires tested, no less than 52 percent of students believe that online practice is safer than regular schools because positions and times are more flexible.